Effects of health education in the elderly with mild cognitive impairment - Francine Golghetto Casemiro; Diana Monteiro Quirino; Maria Angélica Andreotti Diniz; Rosalina Aparecida Partezani Rodrigues; Sofia Cristina Iost Pavarini; Aline Cristina Martins Gratão
ABSTRACT Objective: to analyze the effects of health education on both cognition and depressive/anxiety symptoms in the elderly with Mild Cognitive Impairment (MCI). Method: this is a randomized and controlled clinical trial. Participants (n=22) were recruited from a specialized outpatient clinic, and assigned into two groups: a Health Education Group (HEG) (n=10) and a Control Group (CG) (n=12). The participants were evaluated before and after the intervention, which was composed of classes and dynamics. The intervention consisted of 20 meetings, over a period of five months. The assessment was performed by means of the Addenbrooke's Cognitive Examination - Revised (ACER), the Mini-Mental State Examination to access participant's cognitive state, and the Beck's Scale to access depressive/anxiety symptoms. A Memory Complaints Scale (EQM) was also used. The analysis was carried out using the Student's t test for paired samples. Results: the HEG group demonstrated an improvement in attention/orientation (p= 0,026), memory (p=0.001), language (p= 0.033), and ACE-R (p= 0.003). On the other hand, the CG did not present improvement. Conclusion: the results highlight the importance of non-pharmacological interventions in older adults with MCI to reduce cognitive deficits.